2015
DOI: 10.1371/journal.pone.0120404
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Facility-Level Determinants of Iron and Folic Acid Receipt and Adequate Consumption among Pregnant Women in Rural Bihar, India

Abstract: BackgroundIn Bihar, India, high maternal anemia prevalence and low iron and folic acid supplement (IFA) receipt and consumption have continued over time despite universal IFA distribution and counseling during pregnancy.PurposeTo examine individual and facility-level determinants of IFA receipt and consumption among pregnant women in rural Bihar, India.MethodsUsing District Level Household Survey (2007–08) data, multilevel modeling was conducted to examine the determinants of two outcomes: IFA receipt (any IFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 42 publications
24
49
2
Order By: Relevance
“…CBD of IFA supplementation showed success in reducing anaemia with community-based health workers or volunteers who counselled on health benefits, side-effects and compliance with IFA supplementation. These findings are consistent with other research that found communitylevel workers or volunteers to be instrumental in educating women about common side-effects and how to manage side-effects in order to increase compliance (27,41) . The present review also highlights that CBD of IFA supplementation is a potential platform for encouraging earlier and frequent attendance at ANC, as community-level workers were more likely to identify and reach a greater number of women earlier in pregnancy because women tended not to present to ANC until after the first trimester (27,28,33) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…CBD of IFA supplementation showed success in reducing anaemia with community-based health workers or volunteers who counselled on health benefits, side-effects and compliance with IFA supplementation. These findings are consistent with other research that found communitylevel workers or volunteers to be instrumental in educating women about common side-effects and how to manage side-effects in order to increase compliance (27,41) . The present review also highlights that CBD of IFA supplementation is a potential platform for encouraging earlier and frequent attendance at ANC, as community-level workers were more likely to identify and reach a greater number of women earlier in pregnancy because women tended not to present to ANC until after the first trimester (27,28,33) .…”
Section: Discussionsupporting
confidence: 91%
“…• Motivators for women to take IFA supplements included fear of anaemia risks to mother and child, health benefits, regular follow-up and availability, and inclusion of family members in counselling Wendt et al (27) 2015 India Determinants of IFA supplement receipt from health workers and consumption in pregnant women…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] success rate of previously attempted IFA supplementation strategies. 11,12 This evidential understanding may aid to implement the new strategy efficiently taking care of population dynamics.…”
Section: Introductionmentioning
confidence: 99%